Interregional migration in The Netherlands: an aggregate analysis - Wouter Vermeulen; Eugene Verkade (European Regional Science Association (ERSA), 2003)
The understanding of migration behaviour is of key importance for regional population forecasting. This paper studies the phenomenon empirically, the results are to be applied in a regional labour market model that forecasts the spatial distribution of employment and labour force in the long term. Therefore, we pay particular attention to the impact of local labour market developments. Population forecasting demands for a macro approach to migration. However, certain relations that appear evident from microanalyses are difficult to trace in aggregate data. There are two ways in which we deal with this problem. We distinguish seven age groups. Since some migration motives (like education) are associated with particular age groups, we get a clearer picture of underlying mechanisms. Secondly, we expect that the share of labour motivated migrations in the flow between two regions increases with the distance between them. We therefore consider the impact of explanatory variables both on short and on longer distances. We split the migration decision into a decision to move and a choice of destination. For each age group, we propose a generation model based on population characteristics, that projects the total number of movers per region. The distribution of these migrants is determined by means of a production constrained spatial interaction model. Explanatory variables cover housing, labour market and study motives. Housing market related variables dominate short distance moves. Our estimation results show that labour market variables indeed play a significant role in describing long distance moves of young adults.
Keywords: 330